An Evaluation of the Patent System in Relation to Transfer of Technology in Nigeria - Adedeji, Adewole Adisa (2015)
The study examined the patent system in Nigeria. It assessed the effectiveness of the protection of invention and technical know-how, identifying the shortcomings of the system, and proposed appropriate strategies for legal and institutional reforms. This was with a view to enhancing its role in promoting transfer of technology in Nigeria. The study obtained primary information from judicial decisions, legislation and international conventions: the Patent and Design Act 1970, the Paris Convention for the Protection of Industrial Property of 1883, the Agreement on Trade Related Aspect of Intellectual Property (TRIPS) of 1994, National Office for Technology Acquisition and Promotion (NOTAP) Act, as well as legislation relating to the patent system. Secondary data were obtained from published texts, journals, opinions of intellectual property law scholars, official records, and documents of international institutions like the World Intellectual Property Organisation (WIPO), African Regional Intellectual Property Organisation (ARIPO) etc. Vital information was also gathered from the Patent Registry Abuja, through unstructured interviews conducted with the Registrar of Patent, and the Director of NOTAP. The data collected was also subjected to content analysis. The study showed that Nigeria's current patent regime was formulated during the colonial era, and was never designed to facilitate technological development through the transfer of technology. Important provisions that could have aided technology transfer like utility models were not provided for. Even the relevant provision relating to allied matters like the concept of patentability, were copied almost verbatim from the International Bureau for the Protection of Intellectual Property Model Law on Invention of 1965, without taking into consideration the peculiar nature and needs of Nigeria. The study further revealed that the internal workings and operation of the Patent Registry in Nigeria were not conducive to technology transfer. The Registry as currently organized operated as an archive attached to the Federal Ministry of Commerce, than an industrial property documentation and information centre, that will be responsible for playing the traditional role of rendering and disseminating information on local and international inventive efforts in different fields of invention and technology. Moreover, the Paris Convention of 1883 and the Trade Related Aspect of Intellectual Property Rights (TRIPS) Agreement of 1994, to which Nigeria is a party, were not really in the interest of Nigeria's technological development as some of their provisions were designed to strengthen the hold and control of the developed countries on intellectual property rights. The study also revealed that the operation and practice of NOTAP as a technology transaction regulatory agency was not suitable enough for technology transfer as there was no system of monitoring compliance with its directive on certified technology transfer agreement. In addition, NOTAP's rigid approach on the choice of law governing technology transfer transaction might be harmful to foreign investment and technology transfer in the present age of globalization. The study concluded that the legal and institutional framework of the Nigerian patent system as presently constituted would not be able to play a significant role as a vehicle for the facilitation of transfer of technology.